The Nature of Human is Islamic Perspective and its Implications for Islamic Education - Erik Wiranata; Fairus Aulia; Amrullah Amrullah; Idi Warsah (CV. Publikasi Indonesia, 2025)
This research is a Library Research, previous studies as primary data, which is then analyzed and conclusions can be drawn. research objective is to The first know the nature of man in Islamic perspective. Second, to know the implications of human nature in the Islamic perspective on Islamic education. The results of the study, first, in Islam, humans have a special position as creatures created by Allah SWT who are given reason, spirit, and responsibility in the world. The Qur'an uses three main terms to refer to humans, namely al-insân, al-basyar, and Bani Adam. The Qur'an explains that humans were created through several stages, starting from the ground which then developed into nutfah, alaqah, mudghah, until finally perfected by the inhalation of the spirit by Allah SWT. The purpose of human creation is to recognize and worship Allah, with reason or intellect as a tool for thinking and the heart as a tool for believing in the Essence that cannot be achieved by reason. Second, the implication of human creation with Islamic education has a very close relationship, because Islamic education must be balanced between the science taught and the science of the hereafter. That Islamic education must be based on the concept of human creation in order to have a clear direction in developing human nature in a balanced manner. Human identity as a perfect Muslim can only be realized if all of his potential as a creature of God, educator, learner, servant, and khalifah is well integrated. Islamic education must be based on the integration between qalbiyah (heart) and aqliyah (reason) education in order to form intellectually intelligent and morally superior humans. Islamic education must also be able to develop all human potential through hard skills and soft skills, become a means of transforming Islamic knowledge and culture, and internalize Islamic values in individuals.